First DLSU awards in literature - Student Publications Office - De La Salle University, Manila (Animo Repository, 1986)
The Student Publications Office and the Cultural Arts Program gave a testimonial luncheon and sponsored the first DLSU Awards in Literature. Awards were presented to student writers in the categories of the essay, the short story and poetry.